NOTES ON THE TAXONOMY OF TWO LITTLE KNOWN TAXA OF CURCULIO LINNAEUS, 1758 (Coleoptera, Curculionidae) - Caldara, Roberto; Košťál, Michael; Alonso-Zarazaga, Miguel A. (Fragmenta entomologica, 2012)
Two actions preserve taxal nomenclatural stability within Curculionidae in accordance with the Code. Following the provisions of ICZN Article 23.9.1 Curculio pellitus (Boheman, 1843) (formerly Balaninus) becomes a nomen protectum and Curculio gulosus Fabricius, 1792 a nomen oblitum; Curculio villosus Fabricius, 1781 becomes a nomen protectum and Curculio cerasorum Fabricius, 1775 a nomen oblitum. Having met the conditions of ICZN Article 74 and Article 75, the lectotypes of Curculio gulosus Fabricius, 1792 and Curculio cerasorum Fabricius, 1775, and the neotype of Curculio villosus Fabricius, 1781 are designated. The following new synonymy is proposed: Curculio pellitus (Boheman, 1843) = Curculio gulosus Fabricius 1792 n. syn. and the synonymy Curculio villosus Fabricius, 1781 = Curculio cerasorum Fabricius, 1775 is confirmed